2008
DOI: 10.1007/s10701-008-9252-y
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Quantum Interference Using a Berry’s Phase-like Quantity

Abstract: We show that quantum interference can be interpreted in terms of a phase invariant quantity, not unlike the Berry's phase. Under this interpretation, closed loops in time become fundamental quantum entities, and all quantum states become periodic. Decoherence is then seen to occur naturally as a consequence. This formalism, although counterintuitive, provides another useful way of assigning meaning to quantum probabilities and quasi-probabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 26 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…It was recently shown that QI can be understood heuristically as a quasi-probability effect as opposed to being interference in the traditional sense [11]. Surprisingly, this interpretation requires one to think of closed loops in time (represented by products of probability amplitudes) as fundamental quantum entities, much as we think of state vectors normally.…”
Section: The Closed Loop Perspectivementioning
confidence: 99%
See 4 more Smart Citations
“…It was recently shown that QI can be understood heuristically as a quasi-probability effect as opposed to being interference in the traditional sense [11]. Surprisingly, this interpretation requires one to think of closed loops in time (represented by products of probability amplitudes) as fundamental quantum entities, much as we think of state vectors normally.…”
Section: The Closed Loop Perspectivementioning
confidence: 99%
“…We will calculate the probability P f i for the |i → |f transition two ways: the traditional way, and by the method suggested in [11].…”
Section: The Closed Loop Perspectivementioning
confidence: 99%
See 3 more Smart Citations